Natural Resource Dependence and Monopolized Imports - Arezki, Rabah; Fernandes, Ana; Merchán, Federico; Nguyen, Ha; Reed, Tristan (The Review of Economics and Statistics, 2025)
Abstract Countries with greater commodity export intensity have more concentrated markets for imported goods. Import market concentration is associated with higher domestic prices, suggesting that markups due to greater concentration outweigh any potential cost efficiency. Tariffs, non-tariff measures, and tariff evasion are mechanisms that concentrate import markets. These results suggest a novel channel for the resource curse stemming from the monopolization of imports.